CLASSIFICATION OF TASKS FOR GROUP ROBOTICS FOR METHODS LABOR DIVISION - V. I. Petrenko; F. B. Tebueva; V. O. Antonov (Современная наука и инновации)
At present, technologies and methodological aspects of managing groups of multirobotized systems intensively developed. The full application of decentralized groups of robots requires the solution of several classes of problems, one of which known as the distribution of tasks in a group of robots or the division of labor. Algorithms for the division of labor are diverse and based on a wide range of mathematical methods, many scientific works are devoted to this issue. To systematize the methods of task distribution, this paper analyzes and classifies the tasks to solve for group robotics. In the process of studying the literature on this issue, a pool of tasks obtained that solve certain methods. As a result of the literature review, it is proposed to introduce a classification of tasks based on the specifics of their implementation.